Mystique, langage, image Montrer l'invisible Mystik, Sprache, Bild. Die Visualisierung des Unsichtbaren - Wetzel, René; Wuidar, Laurence; Gedigk, Katharina (Scrinium Friburgense, 2022)
The experience of transcendence, especially when it concerns the direct encounter with God, exceeds every human possibility of expression. Only pictorial expression is able to make visible, at least approximately, what is invisible to the human eye and the human imagination. This volume deals with a whole range of such forms of expression, with contributions from the history of art and literature as well as music and history.